Evaluation of the impact of the mother and infant health project in Ukraine - Olena Y. Nizalova; Maria Vyshnya (Institute for the Study of Labor (IZA), 2009)
This paper exploits a unique opportunity to evaluate the impact of the quality change in the labor and delivery services on maternal and infant health. Since basic medical care has been universally available in Ukraine, implementation of the Mother and Infant Health Project allows addressing quality rather than quantity effect of medical care. Employing program evaluation methods we find that the administrative units participating in the Project have exhibited greater improvements in both maternal and infant health compared to the control rayons. Among the infant health outcomes, the MIHP impact is most pronounced for infant mortality resulted from deviations in perinatal period and respiratory system failures. As for the maternal health, the MIHP is the most effective at addressing anemia, blood circulation, and urinary-genital system complications, as well as late toxicosis. The analysis suggests that the effects are due to early attendance of antenatal clinics, lower share of C-sections, and greater share of normal deliveries, and these effects are causal. Preliminary cost-effectiveness analysis shows enormous benefit per dollar spent on the project: the cost to benefit ratio is one to 122 taking into account both maternal and infant lives saved as well as cost savings due to changes in labor and delivery practices.
Keywords: I12; I18; 330; Maternal health; maternal mortality; infant health; infant mortality; prenatal care; Gesundheitsversorgung; Dienstleistungsqualität; Wirkungsanalyse; Mütter; Kinder; Gesundheit; Kindersterblichkeit; Kosten-Wirksamkeits-Analyse; Ukraine